2022
DOI: 10.2147/ndt.s343844
|View full text |Cite
|
Sign up to set email alerts
|

Victimization in Childhood Influences Presenteeism in Adulthood via Mediation by Neuroticism and Perceived Job Stressors

Abstract: Background: Victimization in childhood profoundly influences the mental health of individuals in adulthood, causing depression, anxiety disorder, suicidality, and self-harm, which leads to productivity loss in the workplace, ie, presenteeism. However, the specific effects of victimization on presenteeism remain unclear. We hypothesized that victimization affects the presenteeism of workers through neuroticism and perceived job stressors and analyzed the association among these factors by path analysis. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In the present study, we analyzed the interrelationships and mediating effects of 4 factors, namely, childhood victimization, and trait anxiety, depressive rumination, and depressive symptoms in adulthood, and found that childhood victimization had a direct and adverse effect on each of the other 3 factors, and had an indirect and adverse effect on depressive symptoms in adulthood through trait anxiety and depressive rumination as mediating factors. To our knowledge, the present study is the first to clarify these mediation effects, and the results are partly consistent with previous findings, including our own [ 11 14 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we analyzed the interrelationships and mediating effects of 4 factors, namely, childhood victimization, and trait anxiety, depressive rumination, and depressive symptoms in adulthood, and found that childhood victimization had a direct and adverse effect on each of the other 3 factors, and had an indirect and adverse effect on depressive symptoms in adulthood through trait anxiety and depressive rumination as mediating factors. To our knowledge, the present study is the first to clarify these mediation effects, and the results are partly consistent with previous findings, including our own [ 11 14 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been noted that intervening and investing in the health, education, and welfare sectors in early childhood brings positive benefits to children, families, and the broader community, and ultimately these benefits lead to increased national productivity and gross domestic product [ 46 ]. Our recent study reported that childhood victimization experiences exacerbate presenteeism in adulthood, with adverse effects on neuroticism and work stressors as mediating factors [ 14 ]. The findings of the present study suggest that the mediating effects of trait anxiety and depressive rumination on adulthood depressive symptoms may be targets for the development of interventions in childhood that will produce long-term positive economic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they reported that the effects of childhood abuse on presenteeism are mediated by the coexistence of current depressive and anxiety disorders. On the other hand, it has also been reported that neuroticism has a mediating effect on the effect of childhood victimization experience on presenteeism ( Hashimoto et al, 2022 ). These previous studies and our present study demonstrate that harmful childhood experiences have a long-term indirect effect on presenteeism in the workplace in adulthood, and that this effect is mediated by anxiety tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a history of childhood abuse affects current presenteeism, and the association is mediated by depression and anxiety ( De Venter et al, 2020 ). Another study reported that experiences of childhood victimization from peers in school or the community affect current presenteeism through neuroticism and perceived job stressors ( Hashimoto et al, 2022 ). Childhood victimization is not childhood abuse, but shares several common features in that both increase neuroticism and depression, and mediate the association between neuroticism and depression ( Tachi et al, 2019 ; Masuya et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%